Single-cell transcriptome dynamics of the autotaxin-lysophosphatidic acid axis during muscle regeneration reveal proliferative effects in mesenchymal fibro-adipogenic progenitors - Contreras, Osvaldo; Harvey, Richard P. (Frontiers in Cell and Developmental Biology, 2023)
Lysophosphatidic acid is a growth factor-like bioactive phospholipid recognising LPA receptors and mediating signalling pathways that regulate embryonic development, wound healing, carcinogenesis, and fibrosis, via effects on cell migration, proliferation and differentiation. Extracellular LPA is generated from lysophospholipids by the secreted hydrolase—ectonucleotide pyrophosphatase/phosphodiesterase 2 (ENPP2; also, AUTOTAXIN/ATX) and metabolised by different membrane-bound phospholipid phosphatases (PLPPs). Here, we use public bulk and single-cell RNA sequencing datasets to explore the expression of Lpar1–6, Enpp2, and Plpp genes under skeletal muscle homeostasis and regeneration conditions. We show that the skeletal muscle system dynamically expresses the Enpp2-Lpar-Plpp gene axis, with Lpar1 being the highest expressed member among LPARs. Lpar1 was expressed by mesenchymal fibro-adipogenic progenitors and tenocytes, whereas FAPs mainly expressed Enpp2. Clustering of FAPs identified populations representing distinct cell states with robust Lpar1 and Enpp2 transcriptome signatures in homeostatic cells expressing higher levels of markers Dpp4 and Hsd11b1. However, tissue injury induced transient repression of Lpar genes and Enpp2. The role of LPA in modulating the fate and differentiation of tissue-resident FAPs has not yet been explored. Ex vivo, LPAR1/3 and ENPP2 inhibition significantly decreased the cell-cycle activity of FAPs and impaired fibro-adipogenic differentiation, implicating LPA signalling in the modulation of the proliferative and differentiative fate of FAPs. Together, our results demonstrate the importance of the ENPP2-LPAR-PLPP axis in different muscle cell types and FAP lineage populations in homeostasis and injury, paving the way for further research on the role of this signalling pathway in skeletal muscle homeostasis and regeneration, and that of other organs and tissues, in vivo.